ChemInform Abstract: Three‐Component C1 Alkynylation of Tetrahydroisoquinolines Catalyzed by Silver Acetate. Issue 48 (December 2015) - Shao, Guang; He, Yanjian; Xu, Ying; Chen, Jian; Yu, Huijuan; Cao, Rihui
Abstract: The title reaction under conditions A) is highly regioselective.